GENETIC VISION OF SOME QUANTITIVE TRAITS IN MUNG BEAN (VIGNA RADIATA L.) SUBJECTED TO CONTRASTING IRRIGATION SITUATIONS - I. R. Noorka; S. F. Abbas; S. Tabasum; S. Rauf (Journal of Animal and Plant Sciences, 2014)
Mung bean is an important legume and pulse crop of semi-arid regions of Pakistan. Therefore, studies were carried out to determine the inheritance of important agronomic traits under contrasting water regimes, Study showed significant genetic variability among parents and their direct and reciprocal crosses. Scaling test showed partially adequacy of additive-dominance model. Genotypes MN-51, MN-92, MN-96, MN-98 and 00TM-12 contained dominant and recessive genes for different quantitative traits, days to first flowering, days to first pod maturity, pod length and Number of grains per pod.
Keywords: Diallel; Dominant; additive; recessive; quantitative; scaling; water stress